Diagnostic evaluation and arrhythmia mechanisms in survivors of unexplained cardiac arrest. Issue 10 (21st August 2019) - Deif, Bishoy; Roberts, Jason D.
Abstract: Identifying the cause of unexplained cardiac arrest is critical for appropriate management of both survivors and their family members. Aborted cardiac arrests whose cause remains unknown following investigation with a surface ECG, echocardiogram, and coronary angiogram are deemed unexplained. Many of these unexplained arrests are felt to be secondary to concealed forms of cardiac channelopathies and latent or subtle cardiomyopathies. This recognition has led to evaluating a diagnostic role for a series of additional investigations, including advanced imaging, genetic testing, and provocative forms of testing, including sodium channel blockade and treadmill testing. Despite evidence of an improved diagnostic yield through their systematic usage, clinical guidelines have yet to endorse a formal algorithm delineating investigations that must be performed before assigning a label of idiopathic ventricular fibrillation, which has resulted in markedly variables thresholds for concluding this diagnosis. Debate remains regarding the need for an invasive electrophysiology study among these patients, though identification of arrhythmic culprits requiring intracardiac electrograms for diagnostic confirmation have suggested a potential role when an initial comprehensive evaluation is unrevealing. Although progress is being made, the sizeable portion of arrests that remain unexplained despite completion of a comprehensive evaluation highlights an ongoing need for further research and additional tools to help unravel the ongoing mysteries of these near fatal events.